2012
DOI: 10.1371/journal.pone.0043416
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Health Inequalities in the Delivery of the Human Papillomavirus Vaccination Programme: Examining the Role of the School Nurse

Abstract: BackgroundHPV immunisation of adolescent girls is expected to have a significant impact in the reduction of cervical cancer. UK The HPV immunisation programme is primarily delivered by school nurses. We examine the role of school nurses in delivering the HPV immunisation programme and their impact on minimising health inequalities in vaccine uptake.Methods and FindingsA rapid evidence assessment (REA) and semi-structured interviews with health professionals were conducted and analysed using thematic analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 49 publications
0
51
0
2
Order By: Relevance
“…The HPV vaccine was introduced as a primary prevention strategy to reduce the incidence of CC (Boyce and Holmes, 2012;Wamai et al, 2013) and two types of HPV vaccine (bivalent for HPV 16 and 18; quadrivalent for HPV 6,11,16 and 18) were approved for use in CC prevention program for reducing the risk of pre-invasive and invasive neoplasia of the cervix (WHO, 2007;Pinar et al, 2010;Makwe and Anorlu, 2011;Uzunlar et al, 2013). It is estimated that the HPV immunization program will reduce deaths from CC by two-thirds if uptake reaches 80%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HPV vaccine was introduced as a primary prevention strategy to reduce the incidence of CC (Boyce and Holmes, 2012;Wamai et al, 2013) and two types of HPV vaccine (bivalent for HPV 16 and 18; quadrivalent for HPV 6,11,16 and 18) were approved for use in CC prevention program for reducing the risk of pre-invasive and invasive neoplasia of the cervix (WHO, 2007;Pinar et al, 2010;Makwe and Anorlu, 2011;Uzunlar et al, 2013). It is estimated that the HPV immunization program will reduce deaths from CC by two-thirds if uptake reaches 80%.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the HPV immunization program will reduce deaths from CC by two-thirds if uptake reaches 80%. Many countries such as the UK, Australia, Canada, France, Greece, New Zealand, Norway and Sweden offer the HPV vaccine as part of their national immunization program (Boyce and Holmes, 2012). The vaccine seems to be safe, well tolerated and effective if the vaccine has to be delivered before exposure to the virus, and preferably, at the preadolescence stage, as the antibody responses are higher Uzunlar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…116 Roughly one-third of adolescents with CMCs, including a disproportionately high number of racial and ethnic minorities from urban settings, have no medical home or a usual source of primary care. 1 office has been associated with a greater odds of influenza vaccination of patients with CMCs.…”
Section: Patientmentioning
confidence: 99%
“…Research in other disadvantaged groups has shown in some populations that HPV vaccination rates are significantly lower in communities with high social deprivation3 and among ethnic minority girls,2 3 girls of travelling families, ‘Looked after Children’, some religious groups and girls who are not in school 4…”
Section: Rates Of Hpv Immunisationmentioning
confidence: 99%